Exposure-related Effects of Pseudomonas fluorescens (Pf-CL145A) on Juvenile Unionid Mussels: U.S. Geological Survey Open-File Report 2015–1066 - Weber, K. L.; Luoma, J. A.; D. A. Mayer; Aloisi, D. B.; Eckert, N. L. (2015)
The exposure-related effects of a commercially prepared spray-dried powder (SDP) or freeze-dried powder (FDP) formulation of Pseudomonas fluorescens (strain CL145A) on the survival of seven species of newly metamorphosed (<72 hours old) freshwater unionid mussels was evaluated. Forty unionid mussels of each species were randomly distributed to test chambers and each species independently exposed for 24 hours to a static dose of either SDP (four species: Lampsilis cardium, Lampsilis siliquoidea, Lampsilis higginsii, and Ligumia recta) or FDP (three species: Obovaria olivaria, Actinonaias ligamentina, and Megalonaias nervosa). Each test chamber was assigned to one of six treatment groups (n = four chambers per group) by using a randomized block design. The six treatment groups included (1) an untreated control group, (2) groups that received applications with nominal target active ingredient (AI) concentrations of 50, 100, 200, and 300 milligrams per liter (mg/L), and (3) a group that received an application with a nominal target AI concentration of 300 mg/L of heat-deactivated test article (300 HD). After a 24-hour exposure period, water inflow to the test chambers was restored, and the unionid mussels were maintained for an additional 7 days before they were assessed for survival. Mean survival of four unionid mussels species exposed to SDP varied among species and treatment groups when compared to the untreated control groups. The results indicate that exposure to SDP-formulated P. fluorescens up to the maximum label concentration (100 mg/L AI) and up to three times the maximum label exposure duration (8 hours) is not likely to affect the survival of L. siliquoidea and L. higginsii. Low mean survival in the L. recta control group (25.0 percent) indicates that results for L. recta should be interpreted with caution. Mean survival of the L. cardium was significantly lower in all treated groups (14.4 to 40.6 percent) compared to the control group (68.8 percent). These results indicate that further investigation on the impact of SDP-formulated P. fluorescens on L. recta and L. cardium is warranted. Mean survival of three unionid mussels species exposed to FDP was not significantly different in the 50-, 100-, and 200-mg/L AI treatment groups and the 300 mg/L heat-deactivated treatment groups when compared to the control groups. Mean survival of O. olivaria and M. nervosa was significantly lower in the 300-mg/L AI treated groups (38.1 and 48.1 percent, respectively) compared to the control groups (71.9 and 88.1 percent, respectively). The results indicate that exposure to FDP-formulated P. fluorescens up to the maximum label concentration (100 mg/L AI) and up to three times the maximum label exposure duration (8 hours) is not likely to affect the survival of O. olivaria, A. ligamentina, and M. nervosa.
Keywords: biology